2011
DOI: 10.1051/medsci/2011276012
|View full text |Cite
|
Sign up to set email alerts
|

Une nouvelle zone de neurogenèse fonctionnelle

Abstract: > En dehors de deux structures précises : la zone sous-granulaire et la zone sous-ventriculaire, le cerveau du mammifère adulte est considéré comme non neurogène, c'est-à-dire incapable de produire de nouveaux neurones. Cependant, les influences environnementales qui s'opposent à cette activité peuvent être mises entre parenthèses dans certaines conditions. C'est ce qui se passe lorsque l'on réalise une neurectomie vestibulaire unilatérale chez le chat adulte. Nos travaux révèlent en effet l'existence d'une ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…Conversely, the lateral VST passes through the posterolateral medulla, corresponding to the reticular formation, then terminates at the anterior portion of lateral funiculus cervical spinal cord. As for the course of the medial and lateral VST, our results appear to agree with animal studies ( Sadjadpour and Brodal, 1968 ; Suzuki, 1985 ; Gullapalli et al, 2006 ; Dutheil et al, 2011 ; Zorner et al, 2014 ; Kasumacic et al, 2015 ). Regarding DTT parameters, the FA value of the medial VST was higher than the lateral VST, while the MD value and tract volume were the opposite.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Conversely, the lateral VST passes through the posterolateral medulla, corresponding to the reticular formation, then terminates at the anterior portion of lateral funiculus cervical spinal cord. As for the course of the medial and lateral VST, our results appear to agree with animal studies ( Sadjadpour and Brodal, 1968 ; Suzuki, 1985 ; Gullapalli et al, 2006 ; Dutheil et al, 2011 ; Zorner et al, 2014 ; Kasumacic et al, 2015 ). Regarding DTT parameters, the FA value of the medial VST was higher than the lateral VST, while the MD value and tract volume were the opposite.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have reported on the anatomical identification of the medial and lateral vestibular nuclei and VST in rat, cat and monkey brain ( Sadjadpour and Brodal, 1968 ; Suzuki, 1985 ; Gullapalli et al, 2006 ; Dutheil et al, 2011 ; Zorner et al, 2014 ; Kasumacic et al, 2015 ). Furthermore, the locations of vestibular nuclei are same with the human and mammal brain, and the course of the medial and lateral VST in the human brain are essentially the same as the mammal brain ( Collier and Buzzard, 1901 ).…”
Section: Discussionmentioning
confidence: 99%
“…12 in Manohar et al 2012). The idea of adult neurogenesis in the brainstem is supported by several studies that showed evidence of “reactive neurogenesis” in the brainstem following vestibular damage (Dutheil et al, 2009, Dutheil et al, 2011b, a). …”
Section: Introductionmentioning
confidence: 93%